Home sanitation facilities and prevalence of diarrhea for children in Oelnasi Village, Kupang Tengah Sub-district - Agustina; Olga Mariana Dukabain; Siprianus Singga; Wanti Wanti; Debora G. Suluh; Fransiskus Geroda Mado (Elsevier, 2021)
Objective: The existence of basic sanitation facilities is still one of the causes of diarrhea disease in East Nusa Tenggara, this study aimed to analyze basic house sanitation facilities and the habit of washing hands with soap on the incidence of diarrhea in children under five. Methods: The research this observational analytic study used a cross sectional design. Samples are 100 houses of children under five in Oelnasi Village. The instrument used in this study was a data collection sheet in the form of a checklist and questionnaire. Results: There were only 3 variables related to the incidence of diarrhea diseases with p < 0.05, i.e. family toilets facilities (OR 0.335, 95% CI: 0.147-0.762), family trash facilities (OR 4.000, 95% CI: 1.229-13.018), and hand washing with soap facilities (OR 0.294, 95% CI: 0.099-0.876). Conclusions: Some sanitation facilities that do not meet the requirements can cause diarrhea in children in Oelnasi Village. It is hoped that the community will pay more attention to basic sanitation hygiene they have, get used to washing their hands with soap before feeding toddlers, throwing garbage in its place, and not letting toddlers defecate in any place.